Lecturers’ Strategies in Teaching Speaking in Intensive Course (IC) Class - Siti Maria Ulfa (Penerbit STKIP PGRI Bangkalan, 2016)
This study is aimed at looking at and investigating lecturer’s strategies in teaching speaking to students in Intensive Course (IC) class. Furthermore, this study also analyzes students’ responses towards the lecturer’ strategies when they are teaching the students. Observation and interview were used to collect data and as a source to know the strategies used by the lecturers. Another instrument was questionnaire used here as supporting data to know students’ responses toward lecturers’ strategies. The result showed that there were several speaking strategies used by them like playing a role, making conversation, drilling, using games and using other creative tasks. While for the students’ response towards the strategies was very positive. They were helped fully to exploit speaking skill to the full by using different varieties of activities.